EVALUATION OF SIGN AND SYMPTOMS RELATED TO INDWELLING URETERAL STENTS - suryawan, joko anom; Danarto, H R; Budiyono, Nur (Indonesian Urological Association, 2016)
Objective: To study factors that influence signs and symptoms related to stented ureter. Material & methods: This was a prospective-cross sectional study, from March 2014 to August 2014, to know factors that influence signs and symptoms of patients with ureteral stent. All patients were inserted ureteral stent participated in this study. Exclusion criteria were patients with malignancy, patients who had history of DJ stent placement previously, patients with bilateral DJ stents and patients with urinary tract infection. All patients completed IPSS questionnaire before inserted stents. After 1 month, when removal DJ stents performed, all patients completed IPSS, USSQ and VAS. All data was analyzed with Chi-square/fisher exact test, Pearson/Spearman correlation and Mann Whitney. Results: Fourty patients consisted of 23 man (57.5%) and 17 women (42.5%) completed this study. The mean age was 44.92 years old and length of stented ureter was 38.22 days. There was significance correlation between IPSS of DJ stent pre-insertion and post insertion (p < 0.001; r = 0.628). Of the patients reported dysuria (62.5%), frequency (55%), nocturia (52.5%), incomplete emptying (47.5%), hematuria (35%) and urgency (15%). On bivariate analysis, there was significance correlation between DJ stent position and frequency (p < 0.001), nocturia (< 0.001), urgency (p = 0.002), incomplete emptying (p = 0.049), dysuria (p = 0.030), hematuria (p = 0.026) and pain (p < 0.001). Conclusion: Previous urinary symptoms and DJ stent position were factors that influenced sign and symptoms related to ureteral stent insertion.